Răspunsuri

2014-10-15T15:01:00+03:00
C=183-126=57
a=183-96=87
b=96-57=39 sau 126-87=39
2014-10-15T15:09:01+03:00

Pai cam asa :

  a+b+c =183                                                                          a+b=126         b+c=96         

  (inlocuim)  in loc de a si c punem relatiile                               a=126-b          c=96-b

126-b+b+96-b=183 (b+b+b = 3b)

126-3b+96=183/+126

3b+96=309/-96

3b=213/:3

b=71=>a=126-b           c=96-b

            a=126-71          c=96-71

            a=55                 c=25      Sper sa te ajute :*